Predictors of breast cancer screening behavior in women aged 20-69 referred to public health centers: A cross-sectional study in Isfahan Province - Fatemeh Ebrahimi; Nasim Roohparvarzadeh; Ghasem Yadegarfar (International Journal of Preventive Medicine, 2022)
Background: Breast cancer is the most common cancer in women. Delay in the diagnosis of breast cancer is a major challenge that can lead to disease progression. Identifying the predictors of breast cancer screening behavior is necessary to promote early detection of breast cancer. This study aims to investigate the predictors of breast cancer screening behavior in women aged 20–69 referred to public health centers. Methods: This cross-sectional study was conducted on 17255 women aged 20–69 years old in Isfahan Province referred to Public Health Centers by the multi-stage random sampling method. data were collected based on the paper forms of women's care aged 20–69 at public health centers, Isfahan, Iran, in 2012. Using STATA 14, logistic regression was employed to explore predictors of breast cancer screening behavior at a 5% significance level. Results: The mean age of women was 36.75 ± 10.46. About 6006 (34.8%) of women had a history of breast self-examination, and among women aged over 40 years, 17.7% reported ever having a mammogram. The most important factors influencing breast self-examination were age 40–49 (OR = 1.18; 95% CI: 1.06-1.33), history of hormone consumption (OR = 1.23; 95% CI: 1.15-1.33), family history of breast cancer in first-degree relatives (OR = 14.22; 95% CI: 9.83-20.57. The most important factors influencing mammography were hormone consumption (OR = 1.26; 95% CI: 1.05-1.51), and family history of breast cancer in first-degree relatives (OR = 32.55; 95% CI: 20.08-52.70). Conclusions: Our findings indicated that the performance of breast self-examination and mammography was low. The frequency of BC screening behavior was higher among women with BC risk factors The results revealed the need for health authorities to pay attention to education in BC detection methods.